2021
DOI: 10.1007/s00421-021-04780-8
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state $$\dot{V}{\text{O}}_{2}$$ above MLSS: evidence that critical speed better represents maximal metabolic steady state in well-trained runners

Abstract: The metabolic boundary separating the heavy-intensity and severe-intensity exercise domains is of scientific and practical interest but there is controversy concerning whether the maximal lactate steady state (MLSS) or critical power (synonymous with critical speed, CS) better represents this boundary. We measured the running speeds at MLSS and CS and investigated their ability to discriminate speeds at which $$\dot{V}{\text{O}}_{2}$$ V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 53 publications
(105 reference statements)
0
29
0
Order By: Relevance
“…For a long time, the maximum lactate steady state (MLSS) was considered as the gold standard for this boundary (Billat et al 2003 ; Keir et al 2015 ; Kilding and Jones 2005 ). However, recent work (Galán-Rioja et al 2020 ; Jamnick et al 2020 ; Jones et al 2019 ; Nixon et al 2021 ) has suggested that CP better estimates the maximal metabolic steady state, the highest power output where a steady state in the oxygen uptake ( O 2 ) response can still be observed, despite increasing blood lactate values (Bräuer and Smekal 2020 ). There is still some debate as to which method (if any) is superior for differentiating between metabolic steady state and non-steady state exercise, and whether both MLSS and CP can actually be used interchangeably (Jones et al 2019 ; Keir et al 2015 ; Nixon et al 2021 ; Poole et al 1988 ).…”
Section: Combining Laboratory and Field Testingmentioning
confidence: 99%
“…For a long time, the maximum lactate steady state (MLSS) was considered as the gold standard for this boundary (Billat et al 2003 ; Keir et al 2015 ; Kilding and Jones 2005 ). However, recent work (Galán-Rioja et al 2020 ; Jamnick et al 2020 ; Jones et al 2019 ; Nixon et al 2021 ) has suggested that CP better estimates the maximal metabolic steady state, the highest power output where a steady state in the oxygen uptake ( O 2 ) response can still be observed, despite increasing blood lactate values (Bräuer and Smekal 2020 ). There is still some debate as to which method (if any) is superior for differentiating between metabolic steady state and non-steady state exercise, and whether both MLSS and CP can actually be used interchangeably (Jones et al 2019 ; Keir et al 2015 ; Nixon et al 2021 ; Poole et al 1988 ).…”
Section: Combining Laboratory and Field Testingmentioning
confidence: 99%
“…It has been suggested that the assumption of the MLSS as an indicator of a steady state whole-body metabolism may be incorrect since steady-state VO 2 behaviour can be observed at intensities slightly above MLSS (Hill et al, 2021;Iannetta et al, 2021;Nixon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the authors conclude that the choice of trial length for CP estimation is arbitrary. However, we argue that when the length of the trial is between 2 and 15 min, CP has repeatedly shown to differentiate intensity domains and steady-state exercise from nonsteady-state exercise 4,5,[7][8][9] . Trials shorter than 2 min or longer than 15 min may not elicit maximal oxygen uptake 10,11 , which is necessary as the CP model applies to the severe-intensity domain.…”
mentioning
confidence: 83%